2004
DOI: 10.1021/np0401361
|View full text |Cite
|
Sign up to set email alerts
|

Two New Chymotrypsin Inhibitors Isolated from the Cyanobacterium Microcystis aeruginosa NIES-88

Abstract: Micropeptins 88-N (1) and 88-Y (2), new 3-amino-6-hydroxy-2-piperidone (Ahp)-containing cyclic depsipeptides, were isolated from Microcystis aeruginosa NIES-88. The structures were elucidated by analyses of HRFABMS, 1D and 2D NMR spectra, and chemical degradation. Micropeptins 88-N and 88-Y inhibited chymotrypsin. The inhibitory activities were closely related to the amino acid residue that was attached to the amino group of Ahp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…It is notable that the Arg/Tyr dichotomy demonstrated here is also found at certain positions in other cyanobacterial metabolite families (in MCs at position 2 and in cyanopeptolins at position 2 adjacent to the 3-amino-6-hydroxy-2-piperidone [Ahp] moiety) and could have functional implications. For example, Yamaki et al (50) have shown that among cyanopeptolins, the dichotomy of basic versus aromatic amino acids is decisive for either trypsin or chymotrypsin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the Arg/Tyr dichotomy demonstrated here is also found at certain positions in other cyanobacterial metabolite families (in MCs at position 2 and in cyanopeptolins at position 2 adjacent to the 3-amino-6-hydroxy-2-piperidone [Ahp] moiety) and could have functional implications. For example, Yamaki et al (50) have shown that among cyanopeptolins, the dichotomy of basic versus aromatic amino acids is decisive for either trypsin or chymotrypsin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nature of this residue is crucial in terms of selectivity and explains its variability. Trypsin shows preference for basic residues (Arg and Lys) while chymotrypsin has preference for large hydrophobic residues (Tyr, Phe, Trp) [47,49,50,51,52]. Abu enhances selectivity for elastase [45].…”
Section: Families Of “Head-to-side-chain” Cyclodepsipetidesmentioning
confidence: 99%
“…Indeed, we have recently identified several cyanobacterial compounds that are potent protease inhibitors, such as grassystatins A–C that selectively inhibit cathepsin E [5] and lyngbyastatins 4–7 [6,7] (see Figure 1) which inhibit porcine pancreatic elastase. The latter group are part of a class prolifically produced by marine and aquatic cyanobacteria [810], containing 3-amino-6-hydroxy-2-piperidone (Ahp) as part of a six-unit cyclic core with a pendant side chain. These generally inhibit certain serine proteases, due to extensive complementarity to the enzymes’ active sites.…”
Section: Introductionmentioning
confidence: 99%